Risk factors for surgical site infection following spinal surgery in Saudi Arabia: A retrospective case–control study. Issue 17 (30th April 2021) - Alghamdi, Saleh; Alawi, Maha; Bokhari, Rakan; Bajunaid, Khalid; Mukhtar, Abdelmoniem; Baeesa, Saleh S.
Abstract : Abstract: Surgical site infections (SSIs) are common complications after spinal surgery that result in increased morbidity, mortality, and healthcare costs. It was estimated that SSIs after spinal surgery resulted in a 4-fold increase in health care costs. The reported SSI rate following spinal surgery remains highly variable between approximately 0.5% and 18%. In this study, we aimed to estimate the SSI rate and identify possible risk factors for SSI after spinal surgery in our Saudi patient population. We conducted a single-center, retrospective case–control study in Saudi Arabia that included patients who developed SSIs, while the controls were all consecutive patients who underwent spinal surgery between January 2014 and December 2016. We extracted data on patient characteristics, anthropometric measurements, preoperative laboratory investigations, preoperative infection prevention measures, intraoperative measures, comorbidities, and postoperative care. We included 201 consecutive patients in our study; their median age was 56.9 years, and 51.2% were men. Only 4% (n = 8) of these patients developed SSIs postoperatively. Postoperative SSIs were significantly associated with longer postoperative hospital stays, hypertension, higher American Society of Anesthesia (ASA) scores, longer procedure durations, and the use of a greater number of blood transfusion units. This study revealed a low SSI rate following spinal surgery. We identified a history of hypertension, prolonged hospitalization, longer operative time, blood transfusion, and higher ASA score as risk factors for SSI in spine surgery in our population. As our findings are from a single institute, we believe that a national research collaboration among multiple disciplines should be performed to provide better estimates of SSI risk factors in our patient population.